Removable friction dampers for low-damage steel beam-to-column joints. Issue 115 (December 2018) - Latour, M.; D'Aniello, M.; Zimbru, M.; Rizzano, G.; Piluso, V.; Landolfo, R.
Abstract: Beam-to-column joints equipped with friction dampers are promising solutions to improve the performance of steel moment resisting frames due to the possibility to guarantee large dissipation capacity limiting the structural damage under severe seismic conditions. In this paper, the experimental tests and the numerical simulations of two types of joints are shown and discussed with the aim of developing pre-qualified configurations. The friction dampers are designed to be easily removable from both the lower beam flange and the column face by means of bolted connections. The devices are composed of a stack of steel plates conceived to assure symmetrical friction. The friction surface is set in vertical direction in first case and in horizontal direction in the second type. The experimental tests confirmed the effectiveness of both examined joints and the finite element analyses allowed characterizing their local response, thus providing additional insights to improve the design requirements. Highlights: The behavior of steel beam-to-column joints equipped with friction dampers is investigated. Dampers with both horizontal and vertical friction surface are investigated. Experimental tests on joints equipped with friction dampers show satisfactory response with negligible damage. The tested joints show non-symmetric response under hogging and sagging moment. Finite element simulations show that the vertical friction damper exhibit plastic deformations lower than the horizontal friction damper.